Fuzzy cognitive maps in estimating the repercussions of oil/gas exploration on politico-economic issues in Cyprus - Schizas, Christos N.; Papaioannou, Maria; Neocleous, Costas (My University, 2011)
Some important politico-economic dynamics, in relation to different scenarios involving the finding and exploitation of oil/gas in the exclusive economic zone of Cyprus, have been modeled and examined through the use of suitable fuzzy cognitive maps. In the interrelated dynamics, various important dynamical parameters have been taken into account, reflecting the interests of the republic of Cyprus, as well as the interests of the Greek and Turkish Cypriot communities. In some respects these interests are antagonistic, while in others could be cooperative. The interests of other countries involved in the Cyprus politicoeconomic problem have also been taken into account. These are primarily Greece, Turkey, United Kingdom, USA, Russia, Israel and the European Union. The main parameters involved in the interrelated dynamics are nationalism, religiousness, knowledge of history, level of educational development, tourism, unemployment, external debt, oil extraction, Anatolian settlers, and the general interests of the countries involved and those of the two communities. The system that has been developed can be used to study the effects of a change in any parameter or a combination of parameters, on the growth and stability of the remaining parameters. Different scenarios on the effects on economies, politics and military involvement have been implemented, observed and appraised.
Keywords: Cyprus problem; Fuzzy cognitive maps; Politico-economic modeling